Patients with myocardial infarction history and nurse’s perspective in a medication adherence intervention adequacy (Research, Society and Development, 2022)
This study identified the conditions increasing the feasibility, acceptability, and effectiveness potential of an intervention to promote the medication adherence. This was a qualitative, cross-sectional study design and a focus group technique with 15 patients and 14 nurses were used to identify the opinion about the intervention to adhere cardioprotective medications in primary healthcare service. The sessions were recorded in audio, transcribed in full, and discussed in detail to obtain agreement among the evaluators. EQUATOR checklist COREQ is used. The participants suggest that the intervention should be applied in a written and verbal way lasting approximately 30 minutes and reinforcement with a thirty-day interval. The forgetting, complexity of the therapeutic regimen, lack of free access to medications, limited understanding of their disease, and the patient's personal choice of not adhering, have been mentioned as barriers to adherence. Participants adjusted the mode of application and dose of the intervention.